Pre-assessment of microbiology quality and antibiotic resistance of vibrio parahaemolyticus from cockle (Anadaragranosa) in Malaysia. - Ariffin, Ahmad Azuhairi; A. M., Sahilah; R., Rahimah; A. S., Norrakiah; A. G., Maaruf; Abdul Rahman, Anita; Ibrahim, Faisal (Malaysian Public Health Specialist Association, 2011)
Introduction Vibrio species has shown one of the most important bacterial diseases in marine cultured organisms, affecting a large number of species of fish and shellfish. Among well known species is Vibrio parahaemolyticus which associated with cockle and reported as one of the important foodborne diseases in developing countries.